A framework for reconstruction of road infrastructure after a disaster. Issue 2 (7th August 2019) - Hayat, Ezri; Haigh, Richard; Amaratunga, Dilanthi
Abstract : Purpose: This paper aims to identify the main aspects requiring immediate attention in the post-disaster reconstruction of road infrastructure, thereby providing a major synthesis, which advances the understanding in this important area. Design/methodology/approach: Literature and empirical evidence obtained from documents and semi-structured interviews with 28 respondents of three case study districts in Aceh, Indonesia was analysed using NVivo 10. The findings were validated through triangulation with the literature and consultation with the experts in the field of disaster management and road infrastructure. Findings: The authors propose a framework for the reconstruction of road infrastructure, which respond to the peculiarities of road projects in a post-disaster setting. The framework comprises various components requiring detailed attention in the reconstruction process and describes their position in the road project and disaster management cycle. Originality/value: The framework fills the gap in the body of knowledge with regard to road infrastructure reconstruction in a post-disaster context. For the first time, this paper recognises the importance of local government capacity in the Aceh Province with regard to the sustainability of the post-disaster reconstruction assets.